PERBANDINGAN METODE WEIGHTED PRODUCT (WP) DAN TOPSIS MENGGUNAKAN MEAN SQUARED ERROR (MSE) (Studi Kasus Program Keluarga Harapan (PKH) di Kelurahan Kotabumi Ilir) - Yuntriani Yuntriani; Novita Sari; Ferry Susanto (Institut Bakti Nusantara, 2026)
The Family Hope Program (PKH) is a conditional social assistance program organized by the Indonesian government to improve the welfare of poor families. However, a non-objective and non-transparent selection process for beneficiaries remains a primary challenge, particularly in Kotabumi Ilir Village. This study aims to compare the performance of two Decision Support System (DSS) methods, Weighted Product (WP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), in determining PKH recipient eligibility using Mean Squared Error (MSE) as an accuracy evaluation metric. This study uses a quantitative approach with primary data from 60 prospective PKH recipient families. Eight criteria were used, including income, family dependents, house condition, asset ownership, employment status, education level, health status, and children's involvement in education. The results show that the MSE of the WP method is 0.435845, while the MSE of TOPSIS is 0.007264, indicating that TOPSIS has a lower prediction error rate and is more accurate in ranking PKH recipients. Nevertheless, the WP method demonstrates simpler computational consistency. These findings recommend implementing the TOPSIS method in the decision support system for determining PKH recipients in Kotabumi Ilir Village.